2016
DOI: 10.1111/evj.12607
|View full text |Cite
|
Sign up to set email alerts
|

Use of the oral sugar test in ponies when performed with or without prior fasting

Abstract: Summary Background It is recommended that the oral sugar test (OST) for insulin dysregulation (ID) be performed after an overnight fast, but fasting is impractical in ponies kept solely at pasture. There are few data on OST repeatability and reliability in ponies. Objectives To report 1) whether OST results obtained in the morning after an overnight fast or without fasting in the afternoon (FASTING/FED) can be used interchangeably, 2) time of highest insulin concentration Tmax[insulin], repeatability and relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 25 publications
1
52
0
1
Order By: Relevance
“…Results of our study indicate that there is good agreement in binary results for insulin concentrations (κ = 0.65 and 0.73 at 60 and 75 minutes, respectively) when the OST is repeated in the same horse. Our results compare favorably with another study that found that the OST had good repeatability (κ = 0.7) when binary (positive/negative) results were examined using an insulin cutoff concentration of 60 μU/mL at 60 and 90 minutes in fasted ponies. Bland‐Altman analysis did not identify any systemic difference in the results obtained from the 2 OSTs, because mean bias values were close to zero for all of the variables evaluated.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Results of our study indicate that there is good agreement in binary results for insulin concentrations (κ = 0.65 and 0.73 at 60 and 75 minutes, respectively) when the OST is repeated in the same horse. Our results compare favorably with another study that found that the OST had good repeatability (κ = 0.7) when binary (positive/negative) results were examined using an insulin cutoff concentration of 60 μU/mL at 60 and 90 minutes in fasted ponies. Bland‐Altman analysis did not identify any systemic difference in the results obtained from the 2 OSTs, because mean bias values were close to zero for all of the variables evaluated.…”
Section: Discussionmentioning
confidence: 92%
“…Testing was performed the following morning, but start times varied among horses and this may have affected results. Insulin concentrations were higher when the OST was performed under fasting conditions in healthy ponies, whereas others were not able to detect an effect of fasting on OST results in horses …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…), being a breed at‐risk of developing EMS, a history of being an easy‐keeper, founder (divergent growth) rings in 1 or more hoof wall, a familial history of laminitis, a dysregulated postprandial serum insulin response to an oral glucose test (OGT) or an oral sugar test (OST), with the choice of dynamic test dependent on the clinician's preference. When this test was performed, a diagnostic cutoff of >60 μIU/mL 60 minutes after the meal was used for the OST, whereas a cutoff value of >80 μIU/mL 2 hours after the meal was used for the OGT …”
Section: Methodsmentioning
confidence: 99%